IMPROVING THE EFFECTIVENESS OF THE RISK MANAGEMENT SYSTEM - I. V. Soklakova; V. V. Gorlov; P. A. Pashkov (Вестник университета, 2021)
The article considers the importance of an effective risk management system in the conditions of uncertainty and instability for Russian companies. It concludeis that it is necessary to implement such a system to improve the management efficiency of a modern organization, using the example of PJSC “Geotek Seismo Razvedka”. The advantages and disadvantages of the existing risk management policy are identified. The authors suggest measures to improve the risk management system for this company. The article proposes to develope (define) the key risk indicators, offers to intensify risk management activities in the field of risk monitoring. To do this, the authors recommend to implement the Omnitracker Risk  Management software product as a system for automating the company’s risk management processes. The advantages of this product are considered, and a schedule for the implementation of Omnitracker Risk Management in PJSC “Geotek Seismo Razvedka”is developed.